Implementasi Supervisi Akademik untuk Meningkatkan Kompetensi Guru dalam Menyusun Administrasi Pembelajaran pada Masa Pandemi Covid-19 di SMP Negeri 6 Mataram - Azizudin, Azizudin (Jurnal Paedagogy, 2022)
This study aims to determine the increase in teacher competence in compiling learning administration during the Covid-19 pandemic through the implementation of academic supervision at SMP Negeri 6 Mataram in the Odd Semester of the 2020/2021 Academic Year. This research method uses school action research conducted for teachers of SMP Negeri 6 Mataram which consists of 58 people. Data were collected by means of observation and questionnaires. The data analysis used is descriptive quantitative and qualitative. The results of this study indicate that the implementation of academic supervision is effectively used to increase teacher competence at SMP Negeri 6 Mataram in preparing learning administration during the Covid-19 pandemic. This result is proven based on the data in the first cycle, the total average value of the teacher's competence only increased from the first cycle, namely the percentage of completeness 44.83% and 91.38%. In cycle II, the teacher is generally said to be complete with the average total score increase is 9.86 and the total percentage increase is 46.55%.